2021
DOI: 10.3390/molecules27010073
|View full text |Cite
|
Sign up to set email alerts
|

The Donor-Dependent and Colon-Region-Dependent Metabolism of (+)-Catechin by Colonic Microbiota in the Simulator of the Human Intestinal Microbial Ecosystem

Abstract: The intestinal absorption of dietary catechins is quite low, resulting in most of them being metabolized by gut microbiota in the colon. It has been hypothesized that microbiota-derived metabolites may be partly responsible for the association between catechin consumption and beneficial cardiometabolic effects. Given the profound differences in gut microbiota composition and microbial load between individuals and across different colon regions, this study examined how microbial (+)-catechin metabolite profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…It has been stated that fecal microbiota from different donors possess different metabolic efficiency of (+)-catechin in our previous research. 34 We estimate the metabolic rate of these donors by calculating the elimination rate constant k after 4 h of incubation based on previously obtained data. 34 On the basis of the obtained k value, it can be concluded that the microbial metabolic rate of (+)-catechin varied greatly among donors, ranging from −0.004 h −1 (donor 9) to 0.200 h −1 (donor 12).…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been stated that fecal microbiota from different donors possess different metabolic efficiency of (+)-catechin in our previous research. 34 We estimate the metabolic rate of these donors by calculating the elimination rate constant k after 4 h of incubation based on previously obtained data. 34 On the basis of the obtained k value, it can be concluded that the microbial metabolic rate of (+)-catechin varied greatly among donors, ranging from −0.004 h −1 (donor 9) to 0.200 h −1 (donor 12).…”
Section: ■ Resultsmentioning
confidence: 99%
“…34 We estimate the metabolic rate of these donors by calculating the elimination rate constant k after 4 h of incubation based on previously obtained data. 34 On the basis of the obtained k value, it can be concluded that the microbial metabolic rate of (+)-catechin varied greatly among donors, ranging from −0.004 h −1 (donor 9) to 0.200 h −1 (donor 12). The variability in metabolic rates leads us to stratify donors 6, 8, 9, and 10 as slow converters to (+)-catechin supplementation, donors 1, 2, 4, and 5 as medium converters, and donors 3, 7, 11, and 12 as fast converters (Table 1).…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, several studies have confirmed that there are substantial interindividual differences in the colonic microbial metabolism of green tea catechins, where potential fast and slow metabolizers may be characterized. 19,64,65 In conclusion, the newly developed PBK model was shown to be able to adequately predict blood concentrations of EGCG and to include the gut microbial metabolism in the model. Although microbial metabolites GA and PG are more capable of inducing Nrf2 pathway activation than EGCG, their contributions to systemic induction of Nrf2-mediated gene expression were predicted to be limited due to their relatively lower systemic concentrations than that of EGCG.…”
Section: ■ Discussionmentioning
confidence: 88%
“…As a member of the flavan-3-ol polyphenol family, catechins are widely distributed in a range of dietary sources, such as tea, cocoa, apple, and kiwi fruit ( 43 , 44 ). Catechins are extremely abundant in polyphenol-rich green tea and its extracts, accounting for approximately one-third of the solids in brewed green tea ( 45 , 46 ).…”
Section: Catechins and Gut Microbiotamentioning
confidence: 99%